Impacts on U.S. Energy Expenditures and Greenhouse-Gas Emissions of Increasing Renewable-Energy Use - Toman, Michael (RAND Corporation, 2008)
How could producing 25 percent of U.S. electricity and motor-vehicle transportation fuels from renewables by the year 2025 affect U.S. consumer energy expenditures and CO2 emissions? This report finds that reaching 25 percent renewables with limited impact on expenditures requires significant progress in renewable-energy technologies and biomass production. Without substantial innovation in these areas, expenditures could increase considerably.